2008
DOI: 10.3732/ajb.2007283
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte diaspore bank: a genetic memory? Genetic structure and genetic diversity of surface populations and diaspore bank in the liverwort Mannia fragrans (Aytoniaceae)

Abstract: Propagule banks are assumed to be able to store considerable genetic variability. Bryophyte populations are expected to rely more heavily on stored propagules than those of seed plants due to the vulnerability of the haploid gametophyte. This reliance has important implications for the genetic structure and evolutionary potential of surface populations. A liverwort, Mannia fragrans, was used to test whether the bryophyte diaspore bank functions as a "genetic memory." If a diaspore bank is capable of conserving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
(81 reference statements)
0
16
2
Order By: Relevance
“…Contrary to our results, it has been shown that the diaspore bank can have similar or higher diversity than the actual forest-floor, both in temperate forests and grasslands (Jonsson, 1993;Hock, 2007;Hock et al, 2008;Vanderpoorten & Goffinet, 2009). In tropical rain forests, a similarly species poor diaspore bank was observed, because of the inhibitory effect of the litter layer (Maciel-Silva et al, 2012).…”
Section: Comparison Of Diaspore Bank and Forestassemblagescontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our results, it has been shown that the diaspore bank can have similar or higher diversity than the actual forest-floor, both in temperate forests and grasslands (Jonsson, 1993;Hock, 2007;Hock et al, 2008;Vanderpoorten & Goffinet, 2009). In tropical rain forests, a similarly species poor diaspore bank was observed, because of the inhibitory effect of the litter layer (Maciel-Silva et al, 2012).…”
Section: Comparison Of Diaspore Bank and Forestassemblagescontrasting
confidence: 99%
“…Most studies have demonstrated that the diaspore bank has similar or greater diversity than the aboveground vegetation (Jonsson, 1993;Rydgren & Hestmark, 1997;Hock et al, 2008). In addition to the aforementioned importance in bryophyte diversity, the role of the bryophyte propagule bank is diverse: ensuring the survival of bryophytes under unfavourable conditions and after disturbance, facilitating regeneration and colonization, and regulating population size (Van Tooren et al, 1990;Jonsson, 1993;Lloret, 1994;During, 1995During, , 1997Hock et al, 2008;Caners et al, 2009;Vanderpoorten & Goffinet, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temporal suitability for some species should provide enough time for their reproduction and dispersal of their progeny unto other soils banks or substrate that allows their "immediate" germination. Genetic material from these propagules at that specific depth may be the factor that aid in these modules survival or fitness [2]. If they fail to reproduce and disperse, then other species would take over and diminish the current moss population and favor another, thus creating a dynamic competition environment.…”
Section: Discussionmentioning
confidence: 99%
“…These banks function as a reservoir of previous generation genetic material [2], which could be produced by spores or/and asexual propagules (i.e. gametophyte fragments, gemmae, etc.).…”
Section: Introductionmentioning
confidence: 99%